2012
DOI: 10.1101/cshperspect.a006635
|View full text |Cite
|
Sign up to set email alerts
|

Arteriovenous Malformations and Other Vascular Malformation Syndromes

Abstract: Vascular malformations are a disruption of the normal vascular pattern in which it is expected that a capillary network of microscopic vessels lies interposed between high-pressure arteries that deliver blood and thin-walled veins that collect low-pressure blood for return to the heart. In the case of arteriovenous malformations, arteries or arterioles connect directly to the venous collection system, bypassing any capillary bed. Clinical consequences result from rupture and hemorrhage, from dramatically incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 61 publications
(71 reference statements)
0
30
0
Order By: Relevance
“…A modified scheme (Table 1), described by Neville [1] divides vascular malformations into: (a) simple (capillary, venous, lymphatic, arteriovenous) or (b) a combination of two or more of the previous categories. Others classify vascular malformations as low flow (capillary, venous and lymphatic malformations or a combination of them) and high flow (arterial and arteriovenous shunt) [1][2][3]. Previous literature reports an incidence of 14-65 % of vascular malformations occurring in the head and neck region [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A modified scheme (Table 1), described by Neville [1] divides vascular malformations into: (a) simple (capillary, venous, lymphatic, arteriovenous) or (b) a combination of two or more of the previous categories. Others classify vascular malformations as low flow (capillary, venous and lymphatic malformations or a combination of them) and high flow (arterial and arteriovenous shunt) [1][2][3]. Previous literature reports an incidence of 14-65 % of vascular malformations occurring in the head and neck region [4].…”
Section: Introductionmentioning
confidence: 99%
“…These lesions normally don't involute, but continue to increase in size in proportion with body size, often reaching enormous volumes [4]. In contrast, Hemangiomas are active proliferating tumors which demonstrate a characteristic pattern of rapid postnatal growth followed by slow involution [2,3]. Although the serendipitous discovery of the therapeutic efficacy of propranolol in the management of infantile hemangiomas has revolutionized the care and outcomes of these lesions [5,6], there is no standard treatment protocol for the management of VM.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic deletion of each of these genes has revealed that they are required for normal vascular development and prevention of AVM formation (6)(7)(8). Mutations in SMAD4, RASA1, and PTEN have also been linked to AVMs in humans (9,10), and mutations in Rasa1 lead to AV shunting in zebrafish (11).…”
mentioning
confidence: 99%
“…(3) Direct connection of arteries or arterioles to the venous system without any capillary bed can be described as arteriovenous malformation and it can be occured sporadically or as a component of inherited vascular malformation syndromes. (4) Arteriovenous malformations may exist for many years without symptoms. (5) Symptoms of fistulas due to malformation differ from congestive heart failure to distal leg ischaemia result to ulcer formation.…”
Section: Discussionmentioning
confidence: 99%